Strategi Guru dalam Pembelajaran Akidah Akhlak untuk Meningkatkan Kesadaran Beragama Siswa SD - Annisa Al Maghirah; Andini Suci Rahmah; Anggina Zahra Salsabilla; Dini Sastra Br Sitorus; Khairin Nazwa; Muhammad Ali Akbar Alfath Nasution; Mahirah Azzah Luthfiyyah; Nurul Khoiriyah; Nur Azizah Chairuna Balqis Tanjung; Novia Syalsa Dila Seja T; Salma Nabila; Shafira Putri Cantika (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Aqidah Akhlak learning strategies in elementary schools are discussed in this study. The purpose of this study is to improve students' learning discipline by using innovative and contextual learning approaches. Aqidah Akhlak plays an important role in shaping students' personality and religious awareness. This research applied a qualitative descriptive approach, which involved the use of observation, interviews, and documentation in data collection. The results showed that effective Aqidah Akhlak learning requires the use of advanced technology, hands-on approaches, exemplary stories, and interactive discussions. Teachers are crucial in providing moral examples and guidance to their students. It is evident that learning methods that relate religious principles to students' daily lives improve students' understanding and application of morals. Students, for example, are educated to maintain cleanliness, resolve conflicts in an Islamic manner, and perform routine worship. In addition, cooperation between students, parents and the environment is essential to build their religious character. According to this research, Aqidah Akhlak education should be designed thoroughly and combine theory, practice and emotional-spiritual approaches. In addition, education should utilize technology as a tool. Therefore, students not only gain a cognitive understanding of religious teachings, but they are also able to internalize the principles in their daily lives, which contributes to the formation of a faithful, pious, and noble generation.